2007
DOI: 10.1108/17439130710756907
|View full text |Cite
|
Sign up to set email alerts
|

Value enhancement using momentum indicators: the European experience

Abstract: In recent years much empirical evidence has been provided on, and many attempts have been made to explain, over-and under-reaction in stock prices which is suggestive that many stocks will oscillate between being over-and under-valued. A number of indicators have been found that prove useful in exploiting these mispricings by identifying cheap stocks to form value portfolios which outperform the market. We establish two characteristics of the individual stocks within these portfolios: (i) the majority of them … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 33 publications
3
15
0
Order By: Relevance
“…Correspondingly, picking the losers among glamour stocks somewhat increases the proportion of stocks that underperform against the stock market average during the following 1-year period. For the sample employed, the average proportion of outperforming stocks in a value winner portfolio is somewhat higher than reported for pure value portfolios in previous studies (for example Piotroski, 2000;Bird and Whitaker, 2003;Bird and Casavecchia, 2007b), while the proportion of outperformers in value loser portfolios is quite in line with the above-mentioned results for pure value portfolios. However, year-to-year comparisons (in Table 3) reveal the considerable differences between the sub-periods.…”
Section: The Added Value Of Combining a Momentum Indicator With Valuesupporting
confidence: 81%
See 1 more Smart Citation
“…Correspondingly, picking the losers among glamour stocks somewhat increases the proportion of stocks that underperform against the stock market average during the following 1-year period. For the sample employed, the average proportion of outperforming stocks in a value winner portfolio is somewhat higher than reported for pure value portfolios in previous studies (for example Piotroski, 2000;Bird and Whitaker, 2003;Bird and Casavecchia, 2007b), while the proportion of outperformers in value loser portfolios is quite in line with the above-mentioned results for pure value portfolios. However, year-to-year comparisons (in Table 3) reveal the considerable differences between the sub-periods.…”
Section: The Added Value Of Combining a Momentum Indicator With Valuesupporting
confidence: 81%
“…Moreover, larger samples of stocks would enable the testing of the impact of various quantile divisions on the results. In addition, the results of Bird and Casavecchia (2007b) show that at least for value strategies based on individual valuation ratios, the performance improvement can be increased including not only price momentum, but also the acceleration rate of the price momentum. Although beyond the scope of this article, the above-mentioned extensions might provide interesting topics for further research.…”
Section: Discussionmentioning
confidence: 95%
“…However, the sales multiples do not indicate whether the sales have been generated without leverage or with maximum leverage, which certainly makes a difference to risks of the firms being compared. In spite of the above‐mentioned disadvantages, evidence has shown that S/P has worked surprisingly well as a relative valuation criterion (e.g., see Bird and Casavecchia, ; Barbee et al ., ; Gharghori et al ., ).…”
Section: Sales‐to‐price (S/p) Anomalymentioning
confidence: 99%
“…Bird and Casavecchia () documented the superiority of S/P in the European markets, but found no evidence of added value from combining valuation ratios. Barbee et al .…”
Section: Sales‐to‐price (S/p) Anomalymentioning
confidence: 99%
See 1 more Smart Citation